The effect of Wordwall-based learning game on junior high school students’ communication and collaboration skills - Aura Relia Fitrah; Yayuk Mulyati; Nasrunniati Dyahayu Anggi Winarni; Eka Nurul Qomaliyah; Rini Anggi Arista; Deny Setiawan (Universitas Muhammadiyah Malang, 2026)
Background-This study provides an overview of the impact of Wordwall-based learning games on students’ communication and collaboration skills. Objectives-The objectives of this research are: (1) Describe the comparison of communication skills between the control class and the experimental class, (2) Describe the comparison of collaboration skills between the control class and the experimental class, (3) The implications of Wordwall-based learning game for improving students’ communication and collaboration skills. Method-The method used is quantitative study employing an experimental approach. The instruments used include observation instruments for assessing communication and collaboration skills by teachers and peers. Results- The results showed that the t-test results for teacher observations on communication skills were 0.071, for peer observations 0.002, as well as teacher observations on collaboration skills at 0.012, and peer observations at 0.222. The results of the t-test indicated significant differences in several aspects, with the experimental class that implemented Wordwall-based learning game being more effective in improving communication and collaboration skills than the control class. Conclusions- Wordwall-based learning game can be used as a learning innovation to improve students' communication and collaboration skills, while also making learning more interactive and contextual. Wordwall-based learning game is not only able to improve communication and collaboration skills, but can also create a fun, interactive, and more meaningful learning experience.